2023
DOI: 10.3389/fendo.2023.1265310
|View full text |Cite
|
Sign up to set email alerts
|

Vanadium, cobalt, zinc, and rubidium are associated with markers of inflammation and oxidative stress in a Greek population with obesity

Charalampia Amerikanou,
Stamatia-Angeliki Kleftaki,
Sotirios Karavoltsos
et al.

Abstract: IntroductionThe prevalence of obesity is rising globally, with negative effects on the socioeconomic system. As a result of its drivers which include low-grade chronic inflammation, oxidative stress, and fatty acid metabolism, this phenotype develops metabolic anomalies that exacerbate its pathogenesis. It has been discovered that metals and metalloids have substantial effects on both the immune system and metabolism and are influenced by factors connected to obesity. Although there is a known connection betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Rubidium is an alkali metal, and its compounds have various chemical and electronic applications. It is not a known nutrient, but its ions are known to have similar properties and the same charge as potassium ions [126].…”
Section: Rubidium (Rb)mentioning
confidence: 99%
“…Rubidium is an alkali metal, and its compounds have various chemical and electronic applications. It is not a known nutrient, but its ions are known to have similar properties and the same charge as potassium ions [126].…”
Section: Rubidium (Rb)mentioning
confidence: 99%
“…The concentration of Co rises with an increase in municipal solid waste (28). Cd, Co, and Pb can induce an inflammatory response in the body through oxidative stress, disrupting the normal functioning of the immune system (29)(30)(31)(32). The experimental result has demonstrated that rats exposed to Pb develop neuroinflammation of microglia in their brains, leading to adverse neurodevelopmental outcomes (33).…”
Section: Introductionmentioning
confidence: 99%